Tissue specificity and mechanism of vitamin D receptor up‐regulation during dietary phosphorus restriction in the rat - Sutin Sriussadaporn (2018)
Dietary phosphorus restriction up‐regulates intestinal vitamin D receptor (VDR), but the tissue specificity of the up‐regulation and the mechanism of receptor accumulation remain unknown. Therefore, the effects of low phosphorus diet (LPD) on VDR content in intestine, kidney, and splenic monocytes/macrophages were examined. Male Sprague‐Dawley rats weighing 50–100 g were fed a normal diet (NPD; 0.6% Ca, 0.65% P) as controls followed by an LPD (0.6% Ca, 0.1% P) for 1–10 days (D1‐D10). LPD rapidly decreased serum P levels by D1 from 11.11 ± 0.19 mg/dl (mean ± SE) to 4.98 ± 0.37 mg/dl (n = 9). LPD increased total serum Ca from 10.54 ± 0.09 mg/dl to 11.63 ± 0.15, 12.17 ± 0.15, and 12.39 ± 0.18 mg/dl by D1, D2, and D3, respectively, and then remained stable. Serum 1,25‐(OH)2D3rapidly increased from 123 ± 5.4 pg/ml to 304 ± 35 pg/ml by D1, reached a plateau through D5, and then gradually increased to 464.9 ± 27.7 pg/ml by D10. Intestinal VDR quantitated by ligand binding assay increased 3.5‐fold from 169.6 ± 13.7 fmol/mg of cytosol protein in rats fed NPD (n = 12) to a peak of 588.3 ± 141.88 fmol/mg of protein by D3 (n = 6; p < 0.001) and then decreased to a plateau level of 2.5‐fold greater than NPD (p < 0.05) during D5 to D10. In contrast, LPD did not up‐regulate kidney or splenic monocyte/macrophage VDR. Northern blot analysis showed that intestinal VDR mRNA increased 2‐fold by D2 (n = 3) of LPD and then gradually decreased to control levels after D5. In contrast, kidney VDR mRNA levels did not change during the first 5 days of P restriction and then subsequently decreased to 50% of NPD controls. The results of these studies indicate that VDR up‐regulation during dietary phosphorus restriction is tissue‐specific and that the mechanism of the up‐regulation is time‐dependent. Acutely (D1‐D5), phosphorus restriction up‐regulates intestinal VDR through increased VDR gene expression, whereas chronic (D5‐D10) phosphorus restriction appears to alter VDR metabolism through nongenomic mechanisms that are consistent with prolongation of the half‐life of the receptor. The nature of the tissue‐specific regulation of VDR during phosphorus restriction remains to be determined. Copyright © 1995 ASBMR